Clinical Pharmacokinetics of Enalapril and Enalaprilat in Pediatric Patients—A Systematic Review - Faisal, Muhammad; Cawello, Willi; Laeer, Stephanie; , The LENA Consortium (Frontiers in Pediatrics, 2021)
Purpose Enalapril has an established safety and efficacy in adults and is used in hypertension, heart failure, and renal failure. In paediatric patients, enalapril is labelled for children with hypertension and used off label in children with heart failure. The systematic literature search aims to assess the current knowledge about enalapril and its active metabolite enalaprilat pharmacokinetics in children as a basis for dose delineation for paediatric patients with heart failure. Method A systematic literature review was performed in the PubMed database using relevant keywords. Results The literature search has resulted in 3 paediatric pharmacokinetic studies of enalapril out of which Wells et al reported about children with hypertension and Nakamura et al 1994, and Llyod et al 1989 presented data for paediatric heart failure patients. The area under the curve values of enalaprilat in hypertensive paediatric patients increased with respect to the age groups and showed maturation of body functions with increasing age. Although the paediatric heart failure patients of greater than 20 days of age showed the area under the curve a similar to that of hypertensive patients, two paediatric patients of very early age (<20 days) were presented with five to six-fold higher area under the curve values. Conclusion Few data related to the pharmacokinetics of enalapril and enalaprilat in hypertensive patients and even less data for heart failure children are available. Substantially more pharmacokinetic studies are required to have reliable and robust enalapril and enalaprilat exposures especially in paediatric patients with heart failure as a basis for any dose delineation.